2019
DOI: 10.18502/kss.v3i17.4669
|View full text |Cite
|
Sign up to set email alerts
|

The Librarian Capability to Implement Information Literacy in Senior High School of Bantul District

Abstract: This research is aimed to describe the school librarian capability to (1) find or collect information, (2) use or utilize information, (3) evaluate information, (4) communicate information, among the senior high schools of Bantul district. The librarian capability to implement information literacy is highly needed since the advancement of information technology and the abundant of information in various social media and other facilities that can support the school activities. It d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many texts emphasise the role of the librarian or school library as one of the elements of information literacy development (Andrews & Saint Hilaire, 2017;Heinström & Sormunen, 2019;Hughes 2018;El-Khayat, 2016;Farmer & Phamle, 2021;Oyediran-Tidings et al 2019;Perryman, 2016;Wahyuningrum et al 2019). Nevertheless, it can be said that the concept of information literacy is changing in some respects.…”
Section: El-khayat 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Many texts emphasise the role of the librarian or school library as one of the elements of information literacy development (Andrews & Saint Hilaire, 2017;Heinström & Sormunen, 2019;Hughes 2018;El-Khayat, 2016;Farmer & Phamle, 2021;Oyediran-Tidings et al 2019;Perryman, 2016;Wahyuningrum et al 2019). Nevertheless, it can be said that the concept of information literacy is changing in some respects.…”
Section: El-khayat 2016mentioning
confidence: 99%
“…This declared discourse contradicts a substantial part of research methods, which often have the character of questionnaires or tests of a substantially objectivist positivist nature (Farmer & Phamle, 2021;Johnson & Barrett, 2017;Ngo et al, 2019;Wahyuningrum et al, 2019). On the other hand, there were no texts with a demanding research design of a qualitative kind or emphasising the complexity of cognition, its dynamism and social and situational anchorage.…”
Section: El-khayat 2016mentioning
confidence: 99%
“…The capabilities such as innovation, tools, information processing, and relationship. An article study by Wahyuningrum, Bustari, and Rahmawati [18] noted that the skills of librarians are badly needed with the advancement of information technology and the wealth of information on various social media and other facilities that can support school activities. The study found that most of the respondents (77.70%) had a good ability to find/collect information to complete the library inventory, 89.96% of the respondents were rated as very capable of library information use/use, 79.73% of them had a good ability to evaluate information and 81.62% of the respondents had a good ability to communicate the information received.…”
Section: Introductionmentioning
confidence: 99%